Phototrophic N2 and CO2 Fixation Using a Rhodopseudomonas palustris-H2 Mediated Electrochemical System With Infrared Photons - Soundararajan, Mathangi; Ledbetter, Rhesa; Kusuma, Paul; Zhen, Shuyang; Ludden, Paul; Bugbee, Bruce; Ensign, Scott A.; Seefeldt, Lance C. (Frontiers in Microbiology, 2019)
A promising approach for the synthesis of high value reduced compounds is to couple bacteria to the cathode of an electrochemical cell, with delivery of electrons from the electrode driving reductive biosynthesis in the bacteria. Such systems have been used to reduce CO2 to acetate and other C-based compounds. Here, we report an electrosynthetic system that couples a diazotrophic, photoautotrophic bacterium, Rhodopseudomonas palustris TIE-1, to the cathode of an electrochemical cell through the mediator H2 that allows reductive capture of both CO2 and N2 with all of the energy coming from the electrode and infrared (IR) photons. R. palustris TIE-1 was shown to utilize a narrow band of IR radiation centered around 850 nm to support growth under both photoheterotrophic, non-diazotrophic and photoautotrophic, diazotrophic conditions with growth rates similar to those achieved using broad spectrum incandescent light. The bacteria were also successfully cultured in the cathodic compartment of an electrochemical cell with the sole source of electrons coming from electrochemically generated H2, supporting reduction of both CO2 and N2 using 850 nm photons as an energy source. Growth rates were similar to non-electrochemical conditions, revealing that the electrochemical system can fully support bacterial growth. Faradaic efficiencies for N2 and CO2 reduction were 8.5% and 23%, respectively. These results demonstrate that a microbial-electrode hybrid system can be used to achieve reduction and capture of both CO2 and N2 using low energy IR radiation and electrons provided by an electrode.